Cartilage rim augmented fascia tympanoplasty: a more effective composite graft model than temporalis fascia tympanoplasty. Issue 6 (11th June 2018) - Kolethekkat, A A; Al Abri, R; Al Zaabi, K; Al Marhoobi, N; Jose, S; Pillai, S; Mathew, J
Abstract: Objective: To validate a newly introduced cartilage rim augmented temporalis fascia tympanoplasty technique by statistically comparing it with the morphological and audiological outcomes of traditional temporalis fascia tympanoplasty. Methods: A retrospective comparative study was conducted on 115 patients who underwent tympanoplasty during 2013 and 2015. Fifty-eight patients underwent temporalis fascia tympanoplasty and 57 underwent cartilage rim augmented fascia tympanoplasty. Results: In the cartilage fascia group, graft healing was achieved in 94.7 per cent of cases; in the temporalis fascia group, the graft take-up rate was 70 per cent. In those with a normal ossicular chain, the post-operative air–bone gap was within 20 dB in 92.6 per cent of cartilage fascia group cases and in 69.7 per cent of the temporalis fascia group cases, which was a statistically significant difference. Among the defective ossicular chain cases, the post-operative air–bone gap was within 20 dB in 76.9 per cent in the cartilage fascia group, as against 57.1 per cent in the temporalis fascia group. Conclusion: Cartilage rim augmented temporalis fascia tympanoplasty has a definite advantage over the temporalis fascia technique in terms of superior graft take up and statistically significant hearing gain in those with normal ossicular mobility.